Elements Of Advocacy In Transport Policy Formulation - Morais, Artur Carlos de; Dourado, Anísio Brasileiro de Freitas; Aragão, Joaquim Jose Guilherme; Yamashita, Yaeko (Archives of Business Research, 2017)
Public transport policies appear to be extremely important in almost every aspect of the life of a community and a major component of the economy. However, their viability is not conditioned only by technical aspects affecting engineering problems or economic viability, as there are other components that contribute to the decision of the public official to act or not to act. The failure in the implementation of viable transport projects, technically and economically, can often be attributed to the lack of these external components to the engineering environment. One such component occurs in the arena of disputes and negotiations between actors. This paper presents a proposal for actions and resources to work on the political viability of transport projects in addition to the technical and economic justification. It draws its theoretical basis from the Policy Cycle model, which defines the decision-making steps and advocacy, along with the actions and resources that make it possible to convince the stakeholders involved. The proposed test was performed for two public policy projects, a public transport operation project and a change in traffic safety legislation. The first and third phases of the Policy Cycle forecast 100% of the items for advocacy action, the barriers to policy, actions to overcome these barriers, and resources that support these actions. In the second phase, the barriers and actions were also 100% forecast, but for the resources that support the forecast actions were low, about 33% for the transport project and 22% for the draft amendment of the legislation.